(untitled) (Research, Society and Development, 2019)
The aim of this research is try to determine the role of Denny Sumargo as a sports ambassador in persuading his followers to participate in physical exercising. Afterwards, this research applied the two-step flow communication theory by Katz and Lazarsfeld. For the method, it uses a qualitative approach with descriptive characteristic. The results found that the Public Relations role that Denny Sumargo undertakes is that of an expert prescriber, communications facilitator, and problem solving process facilitator. However, it can be concluded that there is still a lack of awareness towards the importance of healthy living through exercising and the weak delivery of the message to society.